High selectivity of photocatalytic reduction of CO2 to CO based on terpyridine ligand supported CuI metal organic framework - Zhang, Wen-Dong; Wang, Yun; Liang, Yi; Jiang, Ai-Lin; Gong, Hao; Tian, Xiao-Ying; Fu, Wen-Sheng; Liao, Jia-Zhen; Chen, Peng; Ma, Ying-Zhao (Frontiers in Chemistry, 2022)
In this work, a 4’-(4-cynaophenyl)-4,2’:6’,4-terpyridine supported CuI MOFs photocatalyst (CuI MOF) was applied to the photocatalytic CO2 reduction for the first time. The micro-structural and physicochemical properties of the CuI MOF were systematically studied by the powder X-ray diffraction (PXRD), Single crystal X-ray diffraction (SCXRD), scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FT-IR), UV-Vis diffuse spectroscopy (UV-vis DRS), ns-level photoluminescence spectra (ns-level PL), Ultraviolet photoelectron spectroscopy (UPS), and N2 adsorption-desorption test (BET-BJH). Moreover, the in situ diffuse reflectance infrared fourier transform spectroscopy (in situ DRIFTS) was applied to investigate the adsorption and reaction intermediates of photocatalytic CO2 reduction. As a result, CuI MOF exhibited good performance and outstanding selectivity toward photocatalytic reduction of CO2 to CO under full-spectrum and visible light illumination. Notably, 100% selective photocatalytic conversion of CO2 to CO was achieved. Thus, the study presents the high selectivity and CO2 reduction efficiency of CuI MOF as a potential family of photocatalysts.